Reasons for the absence of students in the last week of study and before and after each holidays in Abha Governorate. - Al - Majathal, Shadia Nasser (Journal of Educational and Psychological Sciences, 2019)
The purpose of this research is to identify the causes of absence and find the appropriate solutions to them and to know the reasons for the problem of the absence of students before and after the holidays and tests and to identify the justifications in Abha governorate. The statistical method was used by building a questionnaire applied to a sample of 550 students, The study found that the most important reasons for repeated absence are due to the reasons for the family and the reasons for the teacher, and that these reasons for absence centered on the factors related to the school environment and family as well as factors related to the same student and student also social factors.
Keywords: education; absence; leave; test; students; school